مساهمة الإبتكارات المالية في تعزيز الإستقرار المالي للمصارف الإسلامية بإستخدام نموذج Z-score لقياس الإستقرار المالي (مصرف السلام للفترة 2016-2020) - بوجمعة, ياسين (جامعة الوادي - University of Eloued, 2023)
The aim of this research paper is to show the role of financial innovations in boosting the financial stability at Assalam Bank from Algeria 2016 to 2020. We have used z-score model in this study It is one of the best qualified models that measures how much safe and stable any bank is. The aim of this study is also to give the meaning of financial innovation at Islamic banks and define the main innovative products at Assalam Bank Algeria. In order to achieve such aim, we depended on the data we have collected from the financial lists of the bank. The study showed a set of findings; among them, which is the most important one that Assalam Bank Algeria is financially stable, That was before exposing the financial innovations in the banking market. Meanwhile, the bank financially kept going stable even after those innovative financial products were exposed. Besides, they positively made Assalam Bank gets benefits which will have a reflection on the financial stability
The contribution of financial innovations in enhancing the financial stability of Islamic banks (Using the z-score model to measure financial stability Al Salam Bank as a model for the period 2016-2020)
مقال
Keywords: الابتكارات المالية؛ المنتجات المبتكرة؛ الاستقرار المالي؛ نموذج z-score؛ المصارف الإسلامية: financial innovations, innovative products, z-score model, Islamic banks.Keywords